Legal Consequences of Franchisees Doing Default Against Franchisors and Legal Protection for Franchisors - Angellina, Pricillia; Urbaniasi, Urbaniasi (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The franchisor and franchisee bond is a reciprocal bond. Because basically the franchisor grants a license to use an IPR in using logos, trademarks, patents, industrial designs, technology, and secret recipes for franchisees. On the franchisee side, of course, they are obliged to provide reciprocity by preparing land, infrastructure and paying a royalty fee to the franchisor. The franchise agreement is subject to Book III of the Civil Code concerning engagement, the legal relationship between the franchisor and the franchisee is also bound by a franchise condition as referred to in the Minister of Trade Regulation Number 71 of 2019 concerning Franchise Operations. The research method used by the author in this study is a normative juridical method, where the approach taken is to use a statutory approach as an object of study to analyze statutory regulations which are the primary source of law in this writing.